2012
DOI: 10.1038/jid.2011.254
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the DNA Copy-Number Genome in the Blood of Cutaneous T-Cell Lymphoma Patients

Abstract: Cutaneous T-cell lymphoma (CTCL) is a heterogeneous non-Hodgkin’s lymphoma that may variably involve the skin, lymph nodes, and peripheral blood. Malignant burden ranges from cutaneous patches and plaques with little evidence of blood involvement to erythroderma often in association with frank leukemia, as in Sézary syndrome. Toward a better understanding of the pathogenesis of this CD4+ T-cell malignancy, we conducted a high-resolution genomic analysis combining DNA (23 samples) and mRNA (12 samples) data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
2
29
0
2
Order By: Relevance
“…4a). This gain correlated with increased TNFRSF1B transcript levels in patient tumor samples and with increased TNFR2 protein levels in the HH CTCL cell line that harbors this gain 18 (Fig. 3c–e and Supplementary Fig.…”
mentioning
confidence: 76%
“…4a). This gain correlated with increased TNFRSF1B transcript levels in patient tumor samples and with increased TNFR2 protein levels in the HH CTCL cell line that harbors this gain 18 (Fig. 3c–e and Supplementary Fig.…”
mentioning
confidence: 76%
“…In CTCL, various cytogenetic studies found multiple genetic alterations that recur in a subset of mycosis fungoides and/or S ezary syndrome patients (36)(37)(38). But few common genetic variants including targetable mutations have been identified (39).…”
Section: Discussionmentioning
confidence: 99%
“…Early cytogenetic studies in CTCL revealed some alterations associated with shorter survival, such as gain of 8q (including MYC) and losses of 6q and 13q (including RB), 17p (TP53), 10 (PTEN, FAS), and 9p21 deletion (including CDKN2A). [16][17][18][19][20] Some of these chromosomal alterations are common to MF and SS, whereas others are more specific, such as gain of chr7 and loss of 9p21 in MF, or gain of 8q and 17q and loss of 10q and 17p in SS. 16,21,22 Massive parallel sequencing technology is a powerful means of better understanding the genetic basis of tumorigenesis and has helped identify new genetic alterations in solid tumors and other hematological malignancies, such as acute myeloid leukemia, [23][24][25] diffuse large B-cell lymphoma, 26,27 Burkitt lymphoma, 28 chronic lymphocytic leukemia, 29,30 and myelodysplastic syndrome.…”
Section: Introductionmentioning
confidence: 99%